2020
DOI: 10.21203/rs.2.22342/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PGRMC1 phosphorylation affects cell shape, motility, glycolysis, mitochondrial form and function, and tumor growth

Abstract: Background: Progesterone Receptor Membrane Component 1 (PGRMC1) is expressed in many cancer cells, where it is associated with detrimental patient outcomes. It contains phosphorylated tyrosines which evolutionarily preceded deuterostome gastrulation and tissue differentiation mechanisms. Results: We demonstrate that manipulating PGRMC1 phosphorylation status in MIA PaCa-2 (MP) cells imposes broad pleiotropic effects. Relative to parental cells over-expressing hemagglutinin-tagged wild-type (WT) PGRMC1-HA, cell… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…This was associated with elevated abundance of some actin-cytoskeletal proteins, increased motility, and dramatic effects on mitochondrial function (4), perhaps reflecting processes underlying those implicated in decidualization. The effect was dependent on Rho-associated protein kinase 1 and accompanied by Y180-dependent PI3K/Akt pathway activity (4). In another study we found that the MAPR interhelical insertion region (MIHIR) in the PGRMC1 Cytb5 domain contains a predicted coiled-coil motif (Fig.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…This was associated with elevated abundance of some actin-cytoskeletal proteins, increased motility, and dramatic effects on mitochondrial function (4), perhaps reflecting processes underlying those implicated in decidualization. The effect was dependent on Rho-associated protein kinase 1 and accompanied by Y180-dependent PI3K/Akt pathway activity (4). In another study we found that the MAPR interhelical insertion region (MIHIR) in the PGRMC1 Cytb5 domain contains a predicted coiled-coil motif (Fig.…”
mentioning
confidence: 92%
“…Because phosphorylation plays an important part in PGRMC1 biology (2,4), and because Salsano et al used bacterially expressed and nonphosphorylated glutathione-S-transferase (GST) labeled PGRMC1 as bait in the coimmunoprecipitation studies, it is difficult to interpret whether all particular identified coprecipitated proteins from cell lysates actually interact with PGRMC1 in cells under the given experimental condition examined, or whether perhaps some interactions with endogenous PGRMC1 were attenuated by treatment, making more protein available to interact with the GST bait protein, or vice versa (Fig. 1).…”
mentioning
confidence: 99%